Exploring the pre and post global financial downturn competitive environments of the private banking markets in Singapore, China and India. - See, Kailing. (2009)
This study seeks to explore the similarities and differences in competitive structures among the private wealth management markets in Singapore, China and India using Michael Porter‘s Five Forces Model. In addition, the impacts of the recent global financial crisis on the markets are also evaluated. The final goal is to recommend a set of strategies that banks can undertake in the short and long term. We obtained secondary data from a wide range of sources, mainly from journals specific to the private wealth management industry. Qualitative data were quantified by using a Five-Point Scale Assessment. From here, within-market and cross-market analyses were carried out. We concluded that India and China were very similar in their competitive structure as compared to Singapore and Singapore was ranked the best across all the forces. Lastly, a four-pronged approach towards relationship management – the key to long term success for a private bank was proposed.